HKS Misinfo Review 2022
DOI: 10.37016/mr-2020-95
|View full text |Cite
|
Sign up to set email alerts
|

Studying mis- and disinformation in Asian diasporic communities: The need for critical transnational research beyond Anglocentrism

Abstract: Drawing on preliminary research about the spread of mis- and disinformation across Asian diasporic communities, we advocate for qualitative research methodologies that can better examine historical, transnational, multilingual, and intergenerational information networks. Using examples of case studies from Vietnam, Taiwan, China, and India, we discuss research themes and challenges including legacies of multiple imperialisms, nationalisms, and geopolitical tensions as root causes of mis- and disinformation; di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In summary, there is no one-size-fits-all solution when it comes to addressing the misinformation problem in a country as diverse as the United States. Our results contribute to confirming findings in recent literature (Austin et al, 2021;Kemei et al, 2022;Lee et al, 2023;Nguyễn et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…In summary, there is no one-size-fits-all solution when it comes to addressing the misinformation problem in a country as diverse as the United States. Our results contribute to confirming findings in recent literature (Austin et al, 2021;Kemei et al, 2022;Lee et al, 2023;Nguyễn et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, recent research on misinformation narratives targeting Black Americans on social media found that anti-vaccine messaging often evokes concerns about medical racism and exploitation (e.g., the Tuskegee syphilis crisis, Dodson et al, 2021) and ongoing structural inequalities (e.g., medical redlining, Andrasfay et al, 2021;racism in healthcare, Diamond et al, 2022) to discourage people from getting vaccinated (Dodson et al, 2021). Harmful narratives discouraging vaccination and endorsing pseudoscientific cures can also be found across Asian American/Pacific Islander and Native American/American Indian communities (Asian American Disinformation Table, 2022;Getahun, 2021;Nguyễn et al, 2022). These examples of misinformation are particularly concerning given ongoing racial disparities in the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is imperative to recognize that communities of color are not monoliths. The experiences of individuals who are part of the Asian diaspora, for example, can vary substantially within and across the Chinese, Vietnamese, and Korean communities (Nguyễn et al, 2022). Furthermore, it may be important to account for generational differences in BIPOC communities (e.g., a recent immigrant vs. a third-generation child).…”
Section: Discussionmentioning
confidence: 99%
“…By considering sociocultural factors, researchers can move beyond a descriptive—and often Anglocentric—understanding of online propaganda production and distribution, reaching more comprehensive conclusions regarding the prominence and significance of specific platforms, actors, and diffusion patterns across different national and subnational context (Camargo and Simon, 2022 ). Supply-side scholars can, therefore, enhance their findings by incorporating these factors into their investigations, thus also responding to recent calls numerous researchers have made to ground online propaganda studies in history, society, culture, and politics to avoid neglecting the role race, ethnicity, language, colonial legacy, gender, and class have in this phenomenon (e.g., Siegel, 2020 ; Kreiss, 2021 ; Kuo and Marwick, 2021 ; Nguỹen et al, 2022 ).…”
Section: Discussion: Bridging Online Propaganda Literaturementioning
confidence: 99%